The critical surf studies reader - Hough-Snee, Dexter Zavalza; Sotelo Eastman, Alexander, 1985- (Duke University Press, 2017)
An innovative exploration of the history and culture of surfing that recasts wave-riding as a complex cultural practice and reclaims the forgotten roles that women, indigenous peoples, and peoples of color have played in the its evolution.